Application of bionic architecture in low-carbon design: a systematic review from nature inspiration to architectural practice - Wang, Xue; Xiao, Lin; Fan, Li; Mokhtar, Noor Aisyah; Mat Sulaiman, Mohd Khairul Azhar (Frontiers in Built Environment, 2025)
In this paper, we systematically review the implications of bionic architecture-a design method derived from biological principles-for the low-carbon transformation of the built environment. Based on a review of 109 studies from 2010 to 2024, we classify biomimetic solutions into three main categories: façade systems, structural optimization, and energy-generating envelopes. These nature-inspired strategies are derived from natural mechanisms, such as termite ventilation, lotus-leaf hydrophobicity, and algae photosynthesis, and offer significant potential to reduce carbon. Reported operational energy savings range from 30% to 60%, and reductions in embodied carbon can reach up to 40%. We harmonize performance metrics (definitions, boundaries, and reporting coverage) and compile published CAPEX/OPEX ranges for representative systems. The results confirm the potential of computational instruments for translating biological principles from living systems to architectural applications through parametric design and performance-based model simulation. We also closely consider other issues in terms of scalability, reliability, and price. To address these issues, the review suggests future work streams, including AI-based bionic design, climate-agile prototypes, and multilevel integration. This work provides a comprehensive reference connecting nature-inspired innovation to quantifiable performance outcomes and supplies actionable guidance for architects, engineers, and policymakers in the pursuit of net zero. By linking biology with architecture, bionic design is presented as a significant approach to achieving sustainable and resilient built environments.